2017
DOI: 10.1080/15379418.2017.1365320
|View full text |Cite
|
Sign up to set email alerts
|

Parents in child custody disputes: Why are they disputing?

Abstract: Since 2000, the number of custody disputes has increased in Sweden. Living in the midst of a parental conflict places the children under great stress. Research on parental conflicts is predominantly theoretical; thus, there is a need for empirical studies to better understand the problems and needs of the children and parents. This article examines parental disputes regarding custody, residence, and access for children, and aims to understand the characteristics of the conflicts behind the disputes. The articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 7 publications
0
16
0
1
Order By: Relevance
“…Sources of conflict between ex‐spouses vary across studies but generally concern children (e.g., access to, time with, discipline, and parenting practices) and money (e.g., child support), and often center on the ways that parents feel entitled to their children, and their place in children's lives, in terms of time and location (Bergman & Rejmer, 2017; Bonach, 2005; Kotila & Schoppe‐Sullivan, 2015). Meta‐analyses have documented few differences in the level of conflict between coparents as a function of custody type (Bauserman, 2012; Leclair et al, 2019)—although Leclair et al (2019) observed that more recent studies (which tend to define joint physical custody as involving equal time sharing, as opposed to 70%–30% time sharing; see also Steinbach, 2019) suggest more conflict under joint than sole physical custody, perhaps reflecting greater interaction between parents than in earlier studies.…”
Section: Introductionmentioning
confidence: 99%
“…Sources of conflict between ex‐spouses vary across studies but generally concern children (e.g., access to, time with, discipline, and parenting practices) and money (e.g., child support), and often center on the ways that parents feel entitled to their children, and their place in children's lives, in terms of time and location (Bergman & Rejmer, 2017; Bonach, 2005; Kotila & Schoppe‐Sullivan, 2015). Meta‐analyses have documented few differences in the level of conflict between coparents as a function of custody type (Bauserman, 2012; Leclair et al, 2019)—although Leclair et al (2019) observed that more recent studies (which tend to define joint physical custody as involving equal time sharing, as opposed to 70%–30% time sharing; see also Steinbach, 2019) suggest more conflict under joint than sole physical custody, perhaps reflecting greater interaction between parents than in earlier studies.…”
Section: Introductionmentioning
confidence: 99%
“…In Norway, between 30 and 40 percent of all children presently experience family break-up or have never lived together with both parents (Statistics Norway, 2020). Beginning in the 1990s, the number of disputes about child-related issues that ended up in court rose considerably in Norway (Koch 2008;Vimblemo, Tobra, Knutsen, Olsen, Gleinsvik & Bush 2016), as it did in many other Western countries (Bergman & Rejmer, 2017;Parkinson, 2011). For separating and divorcing families, a standard estimate is that between ten and 15 percent will end up in a pattern of entrenched conflict between parents (Haddad, Philips & Bone 2016;Helland & Borren, 2015;Hetherington, 2002;Mahrer et al 2018;Wiik, Kitterød, Lyngstad & Lidén 2015).…”
Section: Separation and Divorce In The Norwegian Contextmentioning
confidence: 99%
“…Idag utövar nio av tio föräldrar gemensam vårdnad oberoende av om de lever tillsammans eller inte (SCB statistikdatabas 2019). Resterande hälft av vårdnadsmålen är så kallade high-conflictmål som drivs aktivt av en eller båda föräldrarna, vilka är särskilt utmanande att handlägga för domstol och socialtjänst (Bergman och Rejmer 2017a). Antalet high-conflictmål behöver alltså inte ha ökat nämnvärt sedan barnkonventionen ratificerades.…”
Section: Inledningunclassified